In vitro release of [5-methionine]enkephalin and [5-leucine]-enkephalin from the rat globus pallidus - Bayon, Alejandro (1978)
Endogenous [5-methionine]enkephalin (Metenkephalin) and [5-leucine]enkephalin (Leu-enkephalin) are released from perfused slices of rat globus pallidus by increased K(+) in a Ca(2+)-dependent manner. Tissue perfused for 40 min contained only 26% of the Met-enkephalin and 44% of the Leu-enkephalin found in the freshly dissected tissue. After perfusion, the mean (±SEM) ratio (wt/wt) of Met-enkephalin to Leu-enkephalin was 3.4 ± 0.2 compared with 5.8 ± 0.2 in the fresh tissue. The degradation of trace amounts of synthetic [(3)H]enkephalins in the perfusing medium during stimulated release seems to reflect the accelerated degradation of enkephalin released from the tissue: 63% of the Met-enkephalin and 23% of the Leu-enkephalin were degraded in a medium containing bacitracin (30 μg/ml). The mean ratio (wt/wt) of the Met-enkephalin to the Leu-enkephalin recovered after release by exposure of slices to 50 mM K(+) was 2.7 ± 0.3. When perfusates were corrected for degradation, this ratio increased to about 5.5 which is higher than that found in the perfused tissue. The differences in release, tissue loss, and catabolism of the two enkephalins may be reflecting differences in the metabolic systems operating on the pentapeptides, but this interpretation will have to be validated by in vivo release experiments. In any event these observations strongly suggest that both enkephalins can be considered candidate neurotransmitters in the rat globus pallidus.